Nomads, Traders and Holy Men Along China's Silk Road - Juliano, Annette; Lerner, Judith (Brepols, 2002)
This collection of papers formed part of the symposium, “Nomads, Traders and Holy Men Along China’s Silk Road”, held at the Asia Society in New York on November 9-10, 2001. Although the Silk Road has inspired several important museum exhibitions, none had focused on the Hexi Corridor nor attempted to analyze the complexity of the cross-cultural relationships within China’s borders. Nor had any exhibition focused on the nearly four hundred years of political disunity, nomadic incursions and social upheaval, brought about by the collapse of the great Han dynasty (206 B.C.E.-220 C.E.), that then, after a series of short-lived dynasties, culminated in the reunification of China under the Tang empire (618-906).